Deconstructing Development Discourse: Buzzwords and Fuzzwords - and Cornwall, Andrea; Eade, Deborah (Oxfam & Practical Action Publishing, 2010)
Writing from diverse locations, contributors critically examine some of the key terms in current development discourse. Why should language matter to those who are doing development? Surely, there are more urgent things to do than sit around mulling over semantics?